Position of different nebulizer types for aerosol delivery in an adult model of mechanical ventilation - Hou, Haijia; Xu, Dongyang; Dai, Bing; Zhao, Hongwen; Wang, Wei; Kang, Jian; Tan, Wei (Frontiers in Medicine, 2022)
Background: The optimal positions of different types of nebulizer for aerosol delivery remain unclear. Methods: Three ICU ventilators employing three types of nebulizer were separately connected to a simulated lung to simulate nebulization during invasive ventilation. Assist/control-pressure control(A/C-PC) mode was utilized, with inspiratory pressure (Pi) set to 12 cmH2O and positive end expiratory pressure(PEEP) set to 5 cmH2O, with a target Vt of 500 mL. The bias flow of all ventilators was set to 2 L/min. The three nebulizers were the continuous jet nebulizer (c-JN), the inspiratory synchronized jet nebulizer (i-JN), and the vibrating mesh nebulizer (VMN). The five nebulizer positions were as follows: at the Y-piece (Position 1) and 15 cm from the Y-piece (Position 2) between the endotracheal tube and the Y-piece; at the Y-piece (Position 3) and 15 cm from the Y-piece (Position 4) in the inspiratory limb; and at the humidifier inlet (Position 5). Aerosols were collected with a disposable filter placed at the simulated lung outlet (n=3) and were measured via UV spectrophotometry (276 nm). The measurements were compared under different experimental conditions. Results: The aerosol delivery of c-JN rang 5.33±0.49 ~11.12±0.36%, i-JN rang 7.73±0.76~13.75±0.46%, and VMN rang 11.13±0.56~30.20±1.63%. The higher aerosol delivery: for c-JN~Positions 2(10.95±0.15%), for i-JN~Positions 1 or 2(12.91±0.88% or 13.45±0.42%), for VMN~Positions 4(29.03±1.08%); the lower aerosol delivery: for c-JN~Positions 1, 3 or 5, for i-JN~Positions 4 or 5, for VMN~Positions 5. The highest aerosol delivery was lower than that of i-JN, while the VMN was the highest (all P<0.05). However, no differences were observed between the highest aerosol delivery with c-JN and the lowest aerosol delivery with i-JN; similar results were found between the lowest aerosol delivery with VMN and the highest aerosol delivery with c-JN /i-JN in Avea ventilator. There were no differences in the highest aerosol delivery of each nebulizer among the different ventilators (all P>0.05). Conclusion: During adult mechanical ventilation, type of nebulizer and position influence aerosol delivery efficiency, with no differences between ventilators.